First year midwifery students' experience with self-recorded and assessed video of selected midwifery practice skills at Otago Polytechnic in New Zealand. (January 2018) - McIntosh, Carolyn; Patterson, Jean; Miller, Suzanne
Abstract: Studying undergraduate midwifery at a distance has advantages in terms of accessibility and community support but presents challenges for practice based competence assessment. Student -recorded videos provide opportunities for completing the assigned skills, self-reflection, and assessment by a lecturer. This research asked how midwifery students experienced the process of completing the Video Assessment of Midwifery Practice Skills (VAMPS) in 2014 and 2015. The aim of the survey was to identify the benefits and challenges of the VAMPS assessment and to identify opportunities for improvement from the students' perspective. All students who had participated in the VAMPS assessment during 2014 and 2015 were invited to complete an online survey. To maintain confidentiality for the students, the Qualtrics survey was administered and the data downloaded by the Organisational Research Officer. Ethical approval was granted by the organisational ethics committee. Descriptive statistics were generated and students' comments were collated. The VAMPS provided an accessible option for the competence assessment and the opportunity for self-reflection and re-recording to perfect their skill which the students appreciated. The main challenges related to the technical aspects of recording and uploading the assessment. This study highlighted some of the benefits and challenges experienced by the midwifery students and showed that practice skills can be successfully assessed at distance. The additional benefit of accessibility afforded by video assessment is a new and unique finding for undergraduate midwifery education and may resonate with other educators seeking ways to assess similar skill sets with cohorts of students studying at distance. Highlights: Student self-recorded and self-assessed video may be an alternative to an objective structured clinical examination (OSCE). This assessment provides an accessible option for competence assessment of distance students. Repetition of skills practiced for the assessment may aid student learning of practice skills. Support with computer technology is necessary for students involved in this assessment.